Normative Ethics after Pragmatic Naturalism. (July 2014) - Sager, Alex
Abstract Philip Kitcher presents an ambitious account of pragmatic naturalism that incorporates an explanatory story of the emergence and development of ethics, a metaethical perspective on progress, and a normative stance for moral theorizing. This article contends that Kitcher's normative stance is incompatible with the explanatory and metaethical components of his project. Instead, pragmatic naturalists should endorse a normative ethics that is experimental, grounded in practice, and acutely aware of cognitive and informational limitations. In particular, the ethical project would benefit from endorsing empirical work on participatory democracy for the identification of mechanisms to guide us on deep moral conflicts.